Coexistence of the relaxor-like and ferroelectric behavior in K1-xLixTaO3. (2nd August 2016) - Trybuła, Z.; Dec, J.; Miga, S.; Łoś, Sz.; Trybuła, M.
ABSTRACT: The results of low-temperature linear and nonlinear susceptibilities, polarization measurements and the dc electric field dependence of the dielectric properties of the lithium-doped potassium tantalate K1-x Lix TaO3, x = 0.034 (KLT-3.4%Li) solid solution are presented. The coexistence of the relaxor-like and ferroelectric behavior and different mechanisms leading to either of them are discussed. The observed ferroelectric phase transition is of the first-order type with temperature hysteresis. This transition is due to the off-center motions of Ta ions in the octahedral environment of oxygen ions. Clusters of Li + ions produce a relaxor-like behavior and random electric field. This field reduces the depolarization field and allows off-center motions of Ta ions and an appearance of spontaneous polarization.